PEMANFAATAN PERMAINAN TRADISIONAL DALAM MENGEMBANGKAN KEMAMPUAN MOTORIK SISWA SDN 2 SANGGRAHAN - Besta, Syafiq; Sintiana, Azlia; Firmansyah, Dio Ahmad; Putri, Eka Meilia; Kusumaningrum, Gamma Belya; Ratnaningtyas, Indah Maharani (LPPM Press, 2025)
This study aims to determine the use of traditional games in developing students’ motor skills at SDN 2 Sanggrahan. The research employed a descriptive qualitative approach with observation, interviews, and documentation techniques involving 41 students. The traditional games used were engklek for grades I–II and gobak sodor for grade III. Data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that traditional games have a positive impact on improving students’ gross motor skills, particularly in balance, agility, movement coordination, and muscle strength. Moreover, these games foster teamwork, sportsmanship, and social interaction among students. The study concludes that traditional games are effective learning media that provide enjoyable experiences while stimulating both physical and character development in elementary school children.